2008
DOI: 10.1007/s11461-009-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of natural populations of the endangered plant Euryodendron excelsum H. T. Chang

Abstract: Euryodendron excelsum H. T. Chang is an endangered species of the family Theaceae endemic to China. It is listed as a second-class endangered plant for state protection in the Red Data Book of Plants in the People's Republic of China. The species is restricted to one remnant population with less than 200 individuals in the Bajia region of Yangchun County, Guangdong Province. This study was conducted to determine the status of the population, analyze the past population structure and forecast the future populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…Similar declining recruitment of seedlings has been observed in populations of other Cycas species (James et al 2018). Low seedling recruitment directly threatens the viability of the population, as fewer individuals remain to replace old plants, which in the long term can reduce the number of plants in the population (Shen et al 2009;Dian-pei et al 2012). In contrast, the population from Kurizampa showed more sapling recruitments than older plants, a positive sign for sustainability of the population in the area.…”
Section: Population Structuresupporting
confidence: 58%
“…Similar declining recruitment of seedlings has been observed in populations of other Cycas species (James et al 2018). Low seedling recruitment directly threatens the viability of the population, as fewer individuals remain to replace old plants, which in the long term can reduce the number of plants in the population (Shen et al 2009;Dian-pei et al 2012). In contrast, the population from Kurizampa showed more sapling recruitments than older plants, a positive sign for sustainability of the population in the area.…”
Section: Population Structuresupporting
confidence: 58%
“…Younger adults with a high BP and even several other cardiovascular risk factors rarely have a 10-year risk of 15% or greater but often have high lifetime CVD risk; therefore, selecting treatment goals based on 10-year CVD risk alone may not be ideal. Studies [21][22][23] have found that prolonged exposure to an elevated SBP (120-139 mm Hg) in early adulthood increases the long-term risk of CVD; thus, one could consider using a lower 10-year CVD risk profile or calculate the patient's lifetime risk. Future trials should explore the possible long-term benefits of treating younger patients with an SBP of 120 to 139 mm Hg.…”
Section: Discussionmentioning
confidence: 91%
“…For example, habitat destruction is the main reason for the extirpation of Euryodendron excelsum from Guangxi Province (Appendix 1 and Fig. 1), which is at present surviving only in a small population in Yangchun County, in Guangdong (Shen et al, 2008). Picea neoveitchii, a taxon formerly present in up to 6 provinces according to Flora of China, has reached its current highly threatened status (only 11 mature individuals are remaining; Appendix 1) mainly as a consequence of the combination of overexploitation (due to its use as timber) and habitat fragmentation (Zhang, 2007).…”
Section: Endemism Vs Human Threats As Causes Of Endangermentmentioning
confidence: 99%